A review of real-time software engineering methodologies for developing a wall-climbing robot control firmware - Jawawi, D.N.A; Deris, S; Mamat, R, R (ieee, 2000)

(untitled)
Designing and developing software for autonomous robot control system is a challenging task. Issues related to real-time control, embedded system and artificial intelligence are involved in the software development process. This type of software must be developed with proper software methodology or well-defined development process in order to increase the productivity and quality of the software design and software products. This paper presents a review of two real-time software development methodologies and compares their suitability for developing real-time control software for a wall-climbing robot under development at Universiti Teknologi Malaysia (UTM)